2002
DOI: 10.1097/00001756-200202110-00007
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of somotasensory hand representations following cerebral lesions in humans

Abstract: There is evidence of reorganization of somatotopic maps following cortical lesions in mammals such as monkeys, raccoons and rats. However, there has been a striking lack of research on somatosensory plasticity following cerebral damage in adult humans. We describe two individuals with left hemisphere damage who misperceive the locations of tactile stimuli whose presence or absence they can readily detect.We find that the mislocalizations preserve the relative topography of pre-lesion experiences, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 23 publications
4
37
2
Order By: Relevance
“…Nonetheless, the observation of better-than-chance accuracy in locating undetected stimuli is a necessary (if not sufficient) result to support the conclusion that localization is not contingent on detection. Altogether, the present findings could be taken as demonstrating a double dissociation between tactile detection and localization and are therefore consistent with neuropsychological reports of a double dissociation between these same processes (Paillard et al, 1983;Halligan et al, 1995;Rossetti et al, 1995;Rapp et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, the observation of better-than-chance accuracy in locating undetected stimuli is a necessary (if not sufficient) result to support the conclusion that localization is not contingent on detection. Altogether, the present findings could be taken as demonstrating a double dissociation between tactile detection and localization and are therefore consistent with neuropsychological reports of a double dissociation between these same processes (Paillard et al, 1983;Halligan et al, 1995;Rossetti et al, 1995;Rapp et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…A similar somatosensory deficit (as might be called "numb touch") was reported by Rossetti et al (1995) in their study of a man with a left thalamic lesion. The ability of these patients to locate tactile stimuli in the absence of conscious detection contrasts with classic reports (Head and Holmes, 1911) and more recent demonstrations (Halligan et al, 1995;Rapp et al, 2002) of patients who were unable to accurately locate stimuli that they could successfully detect. The combination of these findings indicates that detecting and locating tactile stimuli are doubly dissociable processes, presumably performed by different neural structures.…”
Section: Introductioncontrasting
confidence: 86%
“…Head and Holmes (1911) first reported a number of patients who, following cortical lesion, were unable to indicate where they had been touched (atopognosia), though their ability to detect that they had been touched was apparently unimpaired. Several authors have suggested that localisation errors mainly involve shifts of perceived location proximal to the actual location of touch (e.g., Critchley, 1953;Halligan et al, 1995;Rapp, Hendel, & Medina, 2002). A more complex pattern of mislocalisations, however, was reported by Denny-Brown, Meyer, and Horenstein (1952) who found in one patient that the perceived locations of touches were funnelled towards the wrist and the ankles, resulting in effective foreshortening of the upper arm and leg.…”
Section: Localisation Of Touch On the Body Surfacementioning
confidence: 97%
“…Attending to which finger was stimulated selectively activated the right temporo-parietal junction in a functional magnetic resonance (fMRI) study (Van Boven, Ingeholm, Beauchamp, Bikle, & Ungerleider, 2005). Finally, neuropsychological and transcranial magnetic stimulation (TMS) studies found that damage or disruption to the parietal cortex impairs the localization of both tactile and noxious stimuli (Paillard, Michel, & Stelmach, 1983;Porro et al, 2007;Rapp et al, 2002).…”
Section: Origin Of the Localization Biasesmentioning
confidence: 99%
“…These biases can be thought of as reflecting a distorted 'perceptual map' of the skin surface (Rapp, Hendel, & Medina, 2002;Trojan et al, 2006). Importantly, biases (i.e.…”
Section: Introductionmentioning
confidence: 99%